Export taxes under Bertrand duopoly - Roger Clarke; David R. Collie (Cardiff University, Cardiff Business School, 2006)
This article analyses export taxes in a Bertrand duopoly with product differentiation, where a home and a foreign firm both export to a third-country market. It is shown that the maximum-revenue export tax always exceeds the optimum-welfare export tax. In a Nash equilibrium in export taxes, the country with the low cost firm imposes the largest export tax. The results under Bertrand duopoly are compared with those under Cournot duopoly. It is shown that the absolute value of the export subsidy or tax under Cournot duopoly exceeds the export tax under Bertrand duopoly.
Keywords: F12; F13; L13; 330; Trade Policy; Imperfect Competition; Oligopoly